The Effect Of Stocking Density On Carcass Weight, Carcass Parts, And Carcass Percentage Of Broiler Chickens In Closed-House - Dewi, Resa Rosliana; Setiawan, Iwan; Putranto, Wendry Setiyadi (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
This research examined the effect of different densities on carcass weight, carcass parts, and carcass percentage. The material used in this research was 200 broiler chickens aged three weeks, reared for 14 days until they were 35 days old. The experimental design used was a Completely Randomized Design (CRD) consisting of 5 treatments and four replications. If the analysis of variance showed an effect of treatment (P<0,05), then Duncan's Multiple Range Test was carried out to determine the effect between treatments. The treatments used were P1 = density of 13 birds/m², P2 = density of 14 birds/m², P3 = density of 15 birds/m², P4 = density of 16 birds/m², and P5 = density of 17 birds/m². The study found that density had no significant effect (P>0,05) on the carcass weight, carcass parts, and carcass percentage. Based on the research results, it can be concluded that a density of 16 birds/m² for broiler chickens kept in closed houses still provides good production performance and meat quality.